Passion and compassion as strategic drivers for sustainable value creation: An ordonomic perspective on social and ecological entrepreneurship - Markus Beckmann; Ingo Pies; Alexandra von Winning (Economic and Environmental Studies (E&ES), 2012)
Passion - in the sense of fervent commitment to action - and compassion - understood as sensitive openness for social and ecological concerns - are not a sure formula for business success. Whether social or ecological entrepreneurs, who find themselves under pressure from market competition, experience advantages or disadvantages, depends crucially on the level at which passion and compassion are brought into play. Competitive advantages are possible if entrepreneurial innovators engage in rule-finding discourses and in rule-setting processes that aim at setting free a previously neglected potential for value creation. To illustrate, this article makes use of a case study in order to elucidate the ordonomic 4-box-matrix, which is a valuable orientation tool for strategic management.
Keywords: 330; social entrepreneurship; value creation; stakeholders; social dilemmas; sustainability; strategic management